ANALISIS KEVALIDAN DAN KEPRAKTISAN PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS PLATFORM GENIALLY KELAS V SEKOLAH DASAR - Nur'aini, Intan Putri; Mukmin, Bagus Amirul; Putri, Kharisma Eka (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This study aims to analyze the validity and practicality of an interactive learning media based on the Genially platform for fifth-grade science subjects, specifically on the topic of the eye and its functions. The research uses a Research and Development (R&D) model with the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). The media development process was carried out systematically according to the ADDIE stages to produce valid and practical learning media. Validation by media and content experts yielded scores of 89% and 90%, respectively, indicating the media is highly valid and suitable for use. Practicality tests through questionnaires given to teachers and students resulted in scores of 92% and 94%, showing the media is highly practical. This media supports the learning process with interactive features that facilitate material comprehension and increase student engagement. Based on these results, this learning media can be considered an effective alternative to improve the quality of elementary school education.